Membunuh Tradisi’: Adegan Musik Metal Dan Subkultur Madura - Raditya, Ardhie (JURNAL SOSIAL : Jurnal Penelitian Ilmu-Ilmu Sosial, 2021)
Abstract— Metal music is not 'easy listening' music. Unlike pop music which is full of "laziness", metal music is full of "explosions" from a musical aspect so, not everyone is able and willing to explore metal music. Because of its aggressive noise, metal music is flourishing in the big cities. Madura, whose society tends to be traditional, is a serious obstacle for its young people who enjoy metal music. Those who enjoy metal music are commonly referred to as "metal youths". So far, there have not been many metal studies in Madura. In fact, Madurese metal youths performed metal music scenes that were no less great than those of outsiders. Therefore, this study seeks to describe scenes of obedience to Madurese metal youths with a musical phenomenology approach, and to explain them from the perspective of subcultural studies. Based on the results of the research, it shows that the scenes of the metalization of Madurese metal youths are not only centered on the musical scene, but also, jump out of the musical scene which shakes the stability of the tradition and the political domination of their religion. Keywords—: Metal Music Scenes; MadureseMetalYouths; Subcultural Studies.